Simplifying Operational Scenario Simulation for CubeSat Mission Analysis Purposes - Carvalho, Pedro Ângelo Vaz De; Ivo, André; Venticinque, Guilherme; Duarte, Gustavo Vicari; Miranda, Matheus; Mattiello-Francisco, Fatima (Anais do Workshop on Validation and Verification of Future Cyber-physical Systems (WAFERS); 2022: Anais do III Workshop on Validation and Verification of Future Cyber-physical Systems, 2022)
The low budget and tight schedule of many CubeSat educational projects make important systems engineering practices unfeasible due to the high cost of the computational infrastructure and commercial software tools, which require long setup and learning times. Simulation of space mission operational scenarios is one of the best practices recommended for system engineers to get familiarity with the expected behavior of the satellite in orbit. This work presents the results of the use of Atom SysVAP, an alternative for mission analysis studies in the context of concept of operation of CubeSat-based space projects. By building their simulation environment on tools like Atom, designers have the flexibility to add complexity to the model according to necessity and achieve reliable initial results in a costless and swift manner.